Transfer Period Of Land Rights Ownership By Foreign Citizen Due To Inheritance - Andyna Susiawati Achmad; Astrid Athina Indradewi (Widya Yuridika, 2023)
Land is an essential natural resource that is very important for the life and livelihood of all living things. Recognizing the importance of the primary need for the land, it is not uncommon for disputes or disputes to arise because of this. The Basic Agrarian Law stipulates that the highest and strongest ownership of land rights, namely property rights, can only be owned by Indonesian citizens. If there are foreign nationals who have ownership rights to land in Indonesia by accident due to inheritance, then within one year the person concerned is required to relinquish his rights. The mechanism of transfer of land rights ownership by foreigners is not really clear enough. Thus, this paper aims to justify and emphasize when the duration starts to be calculated because the laws and regulations do not provide any explanation regarding this. This study uses a normative juridical legal research method based on a literature study on various legal theories and laws and regulations. The problem approach used is the statutory and doctrinal approach. The results of this study are the period of transfer of ownership of land rights by foreign citizens due to inheritance, starting from one year since the acquisition of these rights or the loss of citizenship. Foreign heirs have a period of 1 (one) year since the process of changing the name on the land certificate is not counted since the inheritance is opened or since the inheritance certificate has been issued.